PENGARUH EKUITAS MEREK TERHADAP KINERJA PASAR - rosa rosdiana; Nida Salma Fariani; Riski Putri Anjayani; , Shinta Nurliawan Sari (Marketgram Journal, 2023)
Brand equity refers to an added value contained in a product or service being marketed. This is of course the reason consumers buy or use products from these brands. In addition, companies are also marked to be able to increase their company value, which of course has a positive impact on the long-term success of their company. Therefore, many companies prioritize and prioritize brand equity to maximize market performance. Market performance is defined as an indicator that shows the extent to which a company can maximize the value of shares of companies that have sold in a market capital. This study aims to analyze and understand the effect of equity on market performance with the method of literature study or known as a literature review data sources derived from previous research studies that have relevance and relevance to this research topic. Research results and analysis of various previous literatures show that brand equity has a significant effect on market performance.